2009
DOI: 10.1016/s0828-282x(09)70509-4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of messenger RNA and protein levels of cardiac alpha(1)-adrenergic receptor and angiotensin II receptor subtypes during aging in rats

Abstract: S everal receptor systems coexist in the heart, including the adrenergic receptor (AR) and the angiotensin II receptor (ATR). Among the cardiac adrenoceptor subtypes, it is well known that beta (β)-AR is predominant with respect to mediating positive inotropic and chronotropic effects (it accounts for approximately 75% of the inotropic response); however, a vast body of evidence has accumulated showing that the alpha(1)-AR (α 1 -AR) also plays an important role in causing positive inotropic effects (it account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Studies have suggested roles for reactive oxygen [19] and the RAS [24, 53] paralleling the effectors studied in our acute models of reactive interstitial fibrosis [28, 31]. Importantly, several studies, done primarily in the rat, suggest that the local or intrinsic RAS is activated in the aging heart [17, 18, 22, 23, 53]. A recent study in mice utilized mass spectroscopy to demonstrate a significant augmentation of local Ang II in the aging mouse heart [19].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have suggested roles for reactive oxygen [19] and the RAS [24, 53] paralleling the effectors studied in our acute models of reactive interstitial fibrosis [28, 31]. Importantly, several studies, done primarily in the rat, suggest that the local or intrinsic RAS is activated in the aging heart [17, 18, 22, 23, 53]. A recent study in mice utilized mass spectroscopy to demonstrate a significant augmentation of local Ang II in the aging mouse heart [19].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, there is substantial evidence that the aging heart has an augmented endogenous RAS, including ACE1 and ATR-1 in old rats [17, 18] and cardiac Ang II levels in old mice [19] and rats [20]. Hydroxyproline levels, a marker for collagen content, have been known for many years to be elevated in the old rat heart [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to their results impaired gene transcriptional activity was responsible for the decreased expressions. Their hypothesis was that these alterations contribute to the maintenance of normal contractile function in the senescent heart by compensating cardiac hypertrophy and preserving coronary blood flow [19]. Therefore, these changes might be an adaptive response to aging-associated alterations in the cardiovascular system.…”
Section: Adrenergic Signalingmentioning
confidence: 99%
“…AT1 receptors mediate oxidative stress, fibrosis, myocardial hypertrophy, even age-associated hypertrophy, and a number of actions, which contribute to age-related cardiac remodeling. On the other hand, activation of AT2 receptors is considered to antagonize the AT1 receptor-mediated effects [19]. Moreover, AT2 receptors are suggested to be responsible for a benignant form of cardiovascular remodeling: during AT2 receptor stimulation and AT1 receptor blockade Jones et al reported antigrowth effects on cardiac hypertrophy, fibrosis, and aortic hypertrophy in aged rat hearts [24].…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
See 1 more Smart Citation